Pseudomembranous candidiasis in patient wearing full denture - Nurdiana Nurdiana; M. Jusri (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Oral candidiasis is a common opportunistic infection of the oral cavity caused by an overgrowth of Candida species, the commonest being Candida albicans. Candida albicans is a harmless commensal organism inhabiting the mouths but it can change into pathogen and invade tissue and cause acute and chronic disease. Dentures predispose to infection with Candida in as many as 65% of elderly people wearing full upper dentures. Purpose: The purpose of this case report is to discuss thrush in patient wearing full denture which rapidly developed. Case: This paper report a case of 57 year-old man who came to the Oral Medicine Clinic Faculty of Dentistry Airlangga University with clinical appearance of pseudomembranous candidiasis (thrush). Case Management: Diagnosis of this case is confirmed with microbiology examination. Patient was wearing full upper dentures, and from anamnesis known that patient wearing denture for 24 hours and he had poor oral hygiene. Patient was treated with topical (nystatin oral suspension and miconazole oral gel) and systemic (ketoconazole) antifungal. Patient also instructed not to wear his denture and cleaned white pseudomembrane on his mouth with soft toothbrush. Conclusion: Denture, habit of wearing denture for 24 hours, and poor oral hygiene are predisposing factors of thrush and it can healed completely after treated with topical and systemic antifungal.